Controlling Factors Analyses of Sediment Dispersal From Source-to-Sink Systems of Lacustrine Rift Basin: A Case Study From Paleogene Shahejie-Dongying Formations of Nanpu Sag, Eastern China - Yu, Jifeng; Liu, Tianjiao; Jia, Haibo; Jiang, Zihao; Wei, Shuhao; Li, Yanping; Ma, Shibiao (Frontiers in Earth Science, 2021)
Tectonic activities not only shape the basic stratigraphic framework of rift basins, but also profoundly affect the sediment dispersal in the rift basin. In this study, analysis of heavy mineral assemblages in different periods demonstrates that there are three obvious tectono-sedimentary evolutionary stages in the Paleogene provenance area of Nanpu Sag, and the sand bodies increase from bottom of Paleogene Shahejie (Es3) Formation to top of Dongying (Ed1) Formation in Nanpu Sag. Besides, comprehensively utilize the analyses of seismic interpretation, palynology, heavy mineral and borehole core samples to investigate the controlling factors of sediment dispersal in rift basin. The results reveals that the synergy of evolution of tectonic activity and the adjustment of topography evolution are the main controlling factors of sediment dispersal in Nanpu Sag, while the climate changes was not the main factor. We conclude that increased sediment supply rate reflects the control of tectonic activity played on basin topography, rather than climate fluctuations. The differences in the morphological modification resulting in differential sediment dispersal, which is principally related to the differential extrusion of fault system. The catchment area adjustment, is evidenced by interaction and linkage of boundary fault and complex subsidence history, and the adjustment of topography evolution. Considerated that the interaction and linkage of boundary faults and complex subsidence history are multi-directional and differential evolution of provenance area is universal in intra-continental rift basins which highlight the adjustment of sediment transportation system generated by this characteristic of rift basin and emphasizes the importance of controlling factors analysis in understanding differential sediment dispersal that present in rift basin. Besides, four sets of sediments dispersal pattern were delineated based on different developmental regions in rift basin, which are segmental point + multi-stage breaking slope, single stage breaking slope + axial rift valley, axial breaking slope, and paleo-slope + axial rift valley, respectively. This study have certain guiding significance for the prediction of the spatial distribution of sand bodies in the rift basin and the exploration of potential oil and gas targets in the rift basin.